2016
DOI: 10.1186/s12890-016-0264-7
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound in real life: primary diagnosis and mediastinal staging of lung cancer in patients submitted to thoracic surgery

Abstract: BackgroundSince the first articles published for over 10 years ago, endobronchial ultrasound (EBUS) has gained a strong scientific backing and has been incorporated into routine medical practice in pulmonology and thoracic surgery centers. How is EBUS performing outside the scientific environment, as a diagnostic and mediastinal staging tool in a subset of patients that undergo thoracic surgery, is an interesting question.MethodsThis study evaluated consecutive patients who, during the period from January 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The relationship between the rpEBUS probe position and focus also affects the diagnostic yield of rpEBUS-TBLB. [11][12][13][14][15] Uchimura et al 16 reported that the diagnostic yield when the EBUS probe was within the lesion was as high as 90%, but that diagnostic yield may be reduced to 52% to 55% when the ultrasound probe was adjacent to the lesion. Our study showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the rpEBUS probe position and focus also affects the diagnostic yield of rpEBUS-TBLB. [11][12][13][14][15] Uchimura et al 16 reported that the diagnostic yield when the EBUS probe was within the lesion was as high as 90%, but that diagnostic yield may be reduced to 52% to 55% when the ultrasound probe was adjacent to the lesion. Our study showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have evaluated the introduction of new surgical techniques, such as video-assisted thoracic surgery, video-assisted thoracoscopy, 8 , 9 , and robotics 10 in our country. Improvements in early diagnosis have also been described in our setting, with the use of endoscopic ultrasonography for mediastinal staging, 11 , 12 as well as for the management of more peripheral suspicious lesions 13 that were not previously amenable to a minimally invasive approach. Health care in thoracic oncology referral centers has also been shown to have a positive impact on the prognosis of patients with NSCLC in Brazil, when compared with that in general hospitals.…”
mentioning
confidence: 96%
“…For instance, all patients with nonsquamous histology should routinely undergo profiling 11 . However, those diagnosed with pure squamous, small-cell, or neuroendocrine subtypes have a lower likelihood of EGFR, ALK, or ROS1 aberration.Multiple sampling methods are available for lung cancer diagnosis [12][13][14] . Although minimally invasive procedures are often preferred to minimize the risk to patients, their use must be balanced against successful acquisition of sufficient material for pathologic and molecular evaluation.…”
mentioning
confidence: 99%
“…Multiple sampling methods are available for lung cancer diagnosis [12][13][14] . Although minimally invasive procedures are often preferred to minimize the risk to patients, their use must be balanced against successful acquisition of sufficient material for pathologic and molecular evaluation.…”
mentioning
confidence: 99%